The Value of Managing Acute Pancreatitis With Standardized Order Sets to Achieve "Perfect Care". Issue 3 (March 2021) - Shah, Jimmy; Nwogu, Christiana; Vivian, Elaina; John, Elizabeth S.; Kedia, Prashant; Sellers, Brad; Cler, Leslie; Acharya, Priyanka; Tarnasky, Paul
Abstract : Objectives: We aimed to define perfect care index (PCI) metrics and to evaluate whether implementation of standardized order sets would improve outcomes without increasing hospital-based charges in patients with acute pancreatitis (AP). Methods: This is a retrospective, pre-post, observational study measuring clinical quality, processes of care, and hospital-based charges at a single tertiary care center. The first data set included AP patients from August 2011 to December 2014 (n = 219) before the implementation of a standardized order set (Methodist Acute Pancreatitis Protocol [MAPP]) and AP patients after MAPP implementation from January 2015 to September 2018 (n = 417). The second data set included AP patients (n = 150 in each group) from January 2013 to September 2014 (pre-MAPP) and January 2018 to September 2019 (post-MAPP) to evaluate perfect care between the 2 cohorts after controlling for systemic inflammatory response syndrome at baseline. Length of stay, PCI, and hospital-based charges were measured. Results: The post-MAPP cohort had a significantly shorter length of stay (median, 3 days vs 4 days; P = 0.01). In the second data set, PCI significantly increased after implementation of MAPP order sets (5.3%–35.3%, P < 0.0001). Conclusions: The MAPP order sets increased the value of care by improving clinical outcomes without increasing hospital-based charges.